Immediate Loading of Dental Implants in Partially Edentulous Patients: A Clinical Report - Maria Chatzistavrou, DDS, MS,1 David A. Felton, DDS, MS,2 (Journal of Prosthodontics, 2003)
Immediate loading of dental implants offers attractive advantages for patient and prosthodontist alike.